Systemic chemotherapy and pressurized intraperitoneal aerosol chemotherapy (PIPAC): A case report of a multimodal treatment for peritoneal metastases of pancreatic origin. (2020) - Rotolo, Stefano; Ferracci, Federica; Santullo, Francesco; Lodoli, Claudio; Inzani, Frediano; Abatini, Carlo; Pacelli, Fabio; Di Giorgio, Andrea
Highlights: Integration of PIPAC to systemic chemotherapy can have good tolerance profile. Repeated biopsies performed during PIPAC allowed therapy-response monitoring. Analysis of biopsies performed during PIPAC allowed tailoring of chemotherapy. Integration of PIPAC to systemic chemotherapy can permit good quality of life. Abstract: Introduction: Pancreatic ductal adenocarcinoma (PDAC) with peritoneal metastases (PM) has a dismal prognosis and palliative systemic chemotherapy, which represents the standard treatment option, has significant pharmacokinetics limitations and low efficacy. Pressurized intraperitoneal aerosol chemotherapy (PIPAC) is a new method of drug delivery that is expected to maximize exposure of peritoneal nodules to antiblastic agents. A combination of systemic chemotherapy and PIPAC may be valuable. Presentation of case: A 55 years old male affected by PDAC with synchronous PM underwent a multimodal treatment comprising systemic chemotherapy and PIPAC without any procedural-related adverse events. Tumor genomic profiling evaluation from peritoneal biopsies addressed further tailored systemic chemotherapy. Discussion: The presented case illustrates the possibility of adding PIPAC to systemic chemotherapy with a fair tolerance profile and good quality of life while allowing monitoring of therapy-response and tailoring of the antiblastic treatment.